Motion Control and Obstacle Avoidance of Mobile Robot with Mecanum Wheels - Hassan M. Alwan; Volkov Andrey Nikolavich; Ali Shbani; Kochneva Olga Vladmirovna (International Journal of Technology)
Most current research on motion control and obstacle avoidance for mobile robot (MR) is primarily focused on static obstacle avoidance, with limited attention to detecting as well as avoiding moving obstacle. As a result, significant research is still needed to address the problems associated with movable obstacle avoidance. The difficulty of movable obstacle avoidance is influenced by several factors related to obstacle, including its size, geometric dimensions, velocity, direction of movement, and acceleration. Other parameters related to the kinematics of MR also play a significant role. Therefore, this research aimed to develop a new method of intelligent detection as well as avoidance of movable and static obstacle. To achieve this purpose, wheeled mobile robot (WMR) was equipped with six ultrasonic sensors to detect the distance between the robot and obstacle. Moreover, a new algorithm was developed based on WMR center position (CP), provided by the control system or distances between the obstacle and WMR detected by sensors. This algorithm determined the position and velocity of movable obstacle. According to the outputs related to movable obstacle, WMR avoided collision by altering its path to follow a feasible alternative path, which was planned based on individual priority. This method was simulated in avoidance of static and movable obstacle using MATLAB Simulink program. The results obtained during the analysis showed that the percentage of maximum additional time to avoid the fixed obstacle was 1.15% while movable obstacle was 0.7% of the total time. In addition, the percentage of maximum additional length to avoid the fixed obstacle was 5.52% while movable obstacle was 3.58% of the total desired length. The results were satisfactory compared to previous research, showing that WMR avoided movable obstacle and returned to the desired path faster than in other investigations.